(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the current conditions created for women in our country, the efforts made to enhance women’s social and political activity, and the importance of using digital business opportunities for self-employment in line with contemporary demands. It also discusses some thoughts on the participation of women in state organizations and their creativity during their activities.